2011
DOI: 10.1038/gene.2011.30
|View full text |Cite
|
Sign up to set email alerts
|

Non-HLA genes modulate the risk of rheumatoid arthritis associated with HLA-DRB1 in a susceptible North American Native population

Abstract: Most of the genetic risk for rheumatoid arthritis (RA) is conferred by 'shared epitope' (SE), encoding alleles of HLA-DRB1. Specific North American Native (NAN) populations have RA prevalence rates of 2-5%, representing some of the highest rates estimated worldwide. As many NAN populations also demonstrate a high background frequency of SE, we sought to determine whether other genetic factors contribute to disease risk in this predisposed population. RA patients (n ¼ 333) and controls (n ¼ 490) from the Cree/O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 31 publications
(41 reference statements)
2
24
1
Order By: Relevance
“…In the previous study, two polymorphisms, rs3761847 and rs2900180 in the TRAF1-C5 gene, were analyzed, whereas we performed meta-analyses of the rs10818488, rs3761847, rs2900180 and rs10760130 polymorphisms. We included an additional nine studies (Danoy et al, 2011;El-Gabalawy et al, 2011;Fakhfakh Karray et al, 2012;Han et al, 2009;Hikami et al, 2000;Kurreeman et al, 2010;Mohamed et al, 2012;Plant et al, 2010;Stark et al, 2009;Zhu et al, 2011. Our data were consistent with the results found in the previous study that showed rs3761847 and rs2900180 to be associated with RA in Europeans. Additionally, we revealed associations between rs10818488 and rs10760130 polymorphisms and RA in Europeans.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…In the previous study, two polymorphisms, rs3761847 and rs2900180 in the TRAF1-C5 gene, were analyzed, whereas we performed meta-analyses of the rs10818488, rs3761847, rs2900180 and rs10760130 polymorphisms. We included an additional nine studies (Danoy et al, 2011;El-Gabalawy et al, 2011;Fakhfakh Karray et al, 2012;Han et al, 2009;Hikami et al, 2000;Kurreeman et al, 2010;Mohamed et al, 2012;Plant et al, 2010;Stark et al, 2009;Zhu et al, 2011. Our data were consistent with the results found in the previous study that showed rs3761847 and rs2900180 to be associated with RA in Europeans. Additionally, we revealed associations between rs10818488 and rs10760130 polymorphisms and RA in Europeans.…”
Section: Discussionsupporting
confidence: 95%
“…A total of 17 relevant studies on the TRAF1-C5 polymorphisms in RA met our inclusion criteria (Thomson et al, 2007Barton et al, 2008Chang et al, 2008;Danoy et al, 2011;El-Gabalawy et al, 2011;Fakhfakh Karray et al, 2012;Han et al, 2009;Mohamed et al, 2012;. Plant et al, 2010Plenge et al, 2007;Potter et al, 2007;Stark et al, 2009;Zervou et al, 2008;Zhu et al, 2011.).…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…North American First Nations populations have one of the highest prevalence rates of rheumatoid arthritis in the world. 4 Juvenile rheumatoid arthritis, vasculitis, and reactive arthritis also occur significantly more often in the Aboriginal population than in the Caucasian population according to a Canadian study. 5 The Haida First Nation of British Columbia has one of the highest prevalence rates globally of both human leukocyte antigen (HLA) B27 positivity and of ankylosing spondylitis.…”
mentioning
confidence: 96%
“…These include psychological, hormonal, environmental and genetic factors [2]. RA genetic risk factors can be classified into two groups: major histocompatibility complex (MHC) genes especially Human Leucocyt Antigen (HLA) and non-MHC regions [6]. It is known that RA is associated with certain HLA-DR alleles in different populations [7][8][9].…”
Section: Introductionmentioning
confidence: 99%